2010
DOI: 10.1590/s0101-20612010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Otimização da produção de álcool de mandioca

Abstract: O etanol voltou a ocupar um lugar de destaque no cenário energético do país e do mundo. No caso brasileiro, o álcool renasceu com o surgimento dos carros bicombustíveis, além das várias manifestações de governos e empresas, que mostraram o potencial de mercado e da tecnologia de produção de etanol (OLIVEIRA;VASCONCELOS, 2006). Um dos desafios do Brasil é aumentar a oferta de álcool combustível e buscar novas fontes e/ou métodos para produção de álcool.Uma alternativa à substituição desta matéria-prima é o uso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
0
8
0
2
Order By: Relevance
“…where y l is the sum of the responses of the attributes flavor, color, and aroma; x i and x j are the coded variables 1 and 2 , respectively; and b i is the least square regression coefficient, according to Almeida et al (2010) and Curvelo-Santana et al (2010b).…”
Section: Applying Simulated Annealing Algorithmmentioning
confidence: 99%
“…where y l is the sum of the responses of the attributes flavor, color, and aroma; x i and x j are the coded variables 1 and 2 , respectively; and b i is the least square regression coefficient, according to Almeida et al (2010) and Curvelo-Santana et al (2010b).…”
Section: Applying Simulated Annealing Algorithmmentioning
confidence: 99%
“…This study Shah et al 22 Curvelo-Santana et al 18 Nikolic et al 23 The values of kinetic parameters obtained in this study were higher than those reported in the previous studies (Table 4) 18,22,23 , and ethanol yield (Y P/S ) and productivity (Qp) were 0.48 and 2.83 g.L -1 .h -1 , respectively, after 24 h. However, in the fermentation of starch industry waste hydrolysates containing 15% reducing sugars 22 gave rise to slightly higher alcohol concentration, probably because of the amount of the inoculum used (10% v.v -1 ). It is noteworthy that the fermentation time in this study was the lowest among all.…”
Section: Parametersmentioning
confidence: 65%
“…Once the essay 5 was selected, cassava pulp (600 g) was hydrolyzed producing 170 g.L -1 TRS, the equivalent of 160 g.L -1 glucose (HPLC). Moreover, according to Curvelo-Santana et al 18 , an enzymatic hydrolysis efficiency of 79.4% was estimated, which was achieved merely within 1 h of liquefaction and 2 h of saccharification. Figure 2 shows the mean of four experiments for ethanol production, cell growth and substrate consumption during 24 hours of fermentation.…”
Section: Hydrolysis Of Cassava Pulpmentioning
confidence: 99%
“…Vale salientar que as enzimas utilizadas nesse processo de hidrólise encontram-se em abundância no mercado e com um valor considerado baixo (VALLE et al, 2009). Curvelo-Santana et al (2010) buscaram a otimização do processo de hidrólise do amido de mandioca com α-amilase de A. niger e obtenção do álcool deste xarope. Utilizaram-se a concentração de amido entre 7 e 22 g.L -1 e temperatura entre 30 e 59,1°C.…”
Section: Resultsunclassified